Planning the Green Infrastructure of the Tagus River Estuary in Lisbon Metropolitan Area, Portugal - Oliveira, Rosário (2016)
The Tagus River is the most important and largest watershed of Iberia, with 1007 km long and 81 000 km2 basin, about 30% Portuguese. Understood in a cross-border perspective, it constitutes a valuable resource that brings together relevant biophysical, historical and cultural aspects translated into a huge richness and landscape diversity. The Tagus estuary is the largest wetland area in Portugal and one of the most important in Europe, with an area of 325 km2 and a high status for the conservation of important biodiversity. This estuary corresponds to the core of the Lisbon Metropolitan Area, which is about 3.3% of the national territory and population of roughly 3 million inhabitants. The Landscape Observatory of the Tagus River (LOT) is a coordination structure and dynamics of the "Tagus Cultural Landscape" project, covering the national section of the river and the surrounding landscape. The LOT aims to promote and safeguard the diversity and excellence of the cultural Tagus landscape through its study, the collection, exchange and systematization of information and the establishment of protocols and partnerships between public institutions and local communities in a territorial governance approach (http://obspaisagemtejo.org) (Oliveira et al., 2014). The ultimate goal is to build a bottom-up process that would culminate, in the near future, on the nomination of the Tagus’s Cultural Landscape to the UNESCO. The proposal for its inclusion on the Portuguese indicative